SKOPOS THEORY AND CULTURAL BARRIERS TRANSLATION PERSPECTIVES: NEW VOICE IN CHILDREN'S TRANSLATION - Yesayas Palimau Laratmase; Andy Bayu Nugroho; Andre Agesi (Leksema: Jurnal Bahasa dan Sastra, 2025)
This article explores the use of Skopos theory in translating children’s literature, focusing on how translation choices should be guided by purpose and context. Cultural sensitivity and alignment with the cognitive and emotional needs of children as readers are emphasized, following Oittinen’s (2000) perspective. Skopos theory supports adaptation beyond strict equivalence, offering a flexible approach to meet the needs of child audiences. The proposed method involves three key stages: (1) analysis, to understand the function of translation in the children’s literature context; (2) production, to create context-appropriate and culturally aware translations; and (3) promotion, to support the effectiveness and reliability of culturally sensitive translations. This study offers a practical framework to address linguistic and cultural challenges in translating for children, promoting a more thoughtful and audience-centred approach to children’s literature translation.